Analysis of karst spring discharges during droughts - Fiorillo, Francesco; Guadagno, Francesco Maria (Italian journal of engineering geology and environment, 2010)
<span data-sheets-value=""1":2,"2":"We analysed the spring discharges of a large karst system (Campania, Southern Italy) to determine the relation with periods of poor recharge. Due to the Mediterranean climate and hydrogeological conditions of the aquifers, spring hydrographs corresponding to the system are generally characterised by one annual smoothed peak during spring season and a negligible quick flow component. Insufficient recharge due to poor annual rainfall results in flat spring hydrographs (with no peak) that indicate a continuously decreasing discharge. Flat spring hydrographs reveal a drought, which is characterised by a prolonged shortage of water that induces a reduction in discharge during the following year as well. Droughts also appear to be induced by consecutive years with a rainfall below the average.The historical data have shown that each hydrological year depends on the previous year because annual rainfall series do not have a random character and aquifers have a “memory effect”, which results in spring discharges amplifying the effect of poor rainfall.Due to a long historical series and the specific karst spring regime, a flat hydrograph can be forecast as early as winter, thereby providing a useful tool for water management. The time-lag between rainfall and spring discharges has been utilised to determine the amount of rainfall required to avoid a drought."" data-sheets-userformat=""2":13185,"3":"1":0,"10":1,"11":3,"12":0,"15":"Arial","16":8">We analysed the spring discharges of a large karst system (Campania, Southern Italy) to determine the relation with periods of poor recharge. Due to the Mediterranean climate and hydrogeological conditions of the aquifers, spring hydrographs corresponding to the system are generally characterised by one annual smoothed peak during spring season and a negligible quick flow component. Insufficient recharge due to poor annual rainfall results in flat spring hydrographs (with no peak) that indicate a continuously decreasing discharge. Flat spring hydrographs reveal a drought, which is characterised by a prolonged shortage of water that induces a reduction in discharge during the following year as well. Droughts also appear to be induced by consecutive years with a rainfall below the average.The historical data have shown that each hydrological year depends on the previous year because annual rainfall series do not have a random character and aquifers have a “memory effect”, which results in spring discharges amplifying the effect of poor rainfall.Due to a long historical series and the specific karst spring regime, a flat hydrograph can be forecast as early as winter, thereby providing a useful tool for water management. The time-lag between rainfall and spring discharges has been utilised to determine the amount of rainfall required to avoid a drought.